2022
DOI: 10.1155/2022/7729068
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Travel Flow Differences between Peak Hours with Spatial Model with Endogenous Weight Matrix Using Automatic Vehicle Identification Data

Abstract: The rapid urbanization has brought great challenges to the transportation network. However, travel flow at peak hours is not always the same. It is important to investigate how travel flow differs between peak hours to capture travel flow patterns and influential factors to facilitate traffic management and urban planning. This paper establishes a spatial model with endogenous weight matrix (SARBP-EWM) to investigate the travel flow differences between morning and evening peaks on both weekday and weekend base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…• Population (Almasi & Behnood, 2022;Alves et al, 2021;Feizizadeh et al, 2022;Huang et al, 2016;Mahmud et al, 2019;Wu et al, 2024;Zhou et al, 2022) • Median household income (Huang et al, 2019) • Land use (Almasi & Behnood, 2022;Feizizadeh et al, 2022;Sandoval-Pineda et al, 2022;Wang, Yuan, et al, 2019) • POI (Almasi & Behnood, 2022;Sandoval-Pineda et al, 2022;Wang, Yuan, et al, 2019;Zhou et al, 2022) • Street level (Alves et al, 2021;Feizizadeh et al, 2022;Huang et al, 2016) • Zonal level (Almasi & Behnood, 2022;Huang et al, 2016Huang et al, , 2019Mahmud et al, 2019;Sandoval-Pineda et al, 2022;Wang, Yuan, et al, 2019;Wu et al, 2024;Zhou et al, 2022) Weather data • Precipitation, snow depth, temperature, wind speed, visibility, cloud cover (Alves et al, 2021;Hasan et al, 2022) • Street level (Alves et al, 2021) • Zonal level (Hasan et al, 2022) According to Retting et al (1999) while VMT measures the total miles driven by vehicles within a particular area or over a specific period. Furthermore, running red lights, by either drivers or pedestrians (Retting et al, 1999), can increase crash rates.…”
Section: Feature Category Features Author(s) and Publication Year Scalementioning
confidence: 99%
See 3 more Smart Citations
“…• Population (Almasi & Behnood, 2022;Alves et al, 2021;Feizizadeh et al, 2022;Huang et al, 2016;Mahmud et al, 2019;Wu et al, 2024;Zhou et al, 2022) • Median household income (Huang et al, 2019) • Land use (Almasi & Behnood, 2022;Feizizadeh et al, 2022;Sandoval-Pineda et al, 2022;Wang, Yuan, et al, 2019) • POI (Almasi & Behnood, 2022;Sandoval-Pineda et al, 2022;Wang, Yuan, et al, 2019;Zhou et al, 2022) • Street level (Alves et al, 2021;Feizizadeh et al, 2022;Huang et al, 2016) • Zonal level (Almasi & Behnood, 2022;Huang et al, 2016Huang et al, , 2019Mahmud et al, 2019;Sandoval-Pineda et al, 2022;Wang, Yuan, et al, 2019;Wu et al, 2024;Zhou et al, 2022) Weather data • Precipitation, snow depth, temperature, wind speed, visibility, cloud cover (Alves et al, 2021;Hasan et al, 2022) • Street level (Alves et al, 2021) • Zonal level (Hasan et al, 2022) According to Retting et al (1999) while VMT measures the total miles driven by vehicles within a particular area or over a specific period. Furthermore, running red lights, by either drivers or pedestrians (Retting et al, 1999), can increase crash rates.…”
Section: Feature Category Features Author(s) and Publication Year Scalementioning
confidence: 99%
“…Socioeconomic factors are also critical to understanding the causes of car accidents. Prior research has revealed that population, employment rates, and the number of uneducated residents (Almasi & Behnood, 2022;Alves et al, 2021;Feizizadeh et al, 2022;Huang et al, 2016;Mahmud et al, 2019;Wu et al, 2024;Zhou et al, 2022), as well as median household income (Huang et al, 2019), correlate with pedestrian accidents. In addition, specific land use and points of interest, such as hospitals and schools, have been shown to affect traffic accidents in TAZs, according to studies conducted by Almasi and Behnood (2022) Some studies mentioned in Table 2 focus on constructing models for macro-scale accident prediction, using TAZ as the unit of analysis.…”
Section: Feature Category Features Author(s) and Publication Year Scalementioning
confidence: 99%
See 2 more Smart Citations
“…Tus, the panel data model aids in identifying the efects of time trends, observed individual diferences, and endogeneity, thereby providing a more comprehensive understanding and quantifcation of the impact of projects such as the economic externalities of HSR [30,31]. Failure to capture the impact of policies at a certain time node is a drawback of the panel data model [15,32]. Spatial econometric models focus on the interrelationships of infuencing factors within geographic space [6,35].…”
Section: Huang and Xumentioning
confidence: 99%